PERANCANGAN APLIKASI WORKLOAD MEASUREMENT ANALYSIS (WMA) BERBASIS ANDROID UNTUK PERHITUNGAN BEBAN KERJA PEREKAM MEDIS DI RSI AMINAH BLITAR - Shofa Athur Rosyida; Dea Allan Karunia Sakti; Rahmadyo Yudhi Prabowo (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
Workload problems are common in the health sector, one of which is at RSI Aminah, Blitar City. Workload problems are often found in the healthcare, which include manual calculation, a lack of awareness of the formula for workload calculation analysis, and infrequent evaluation, which lead to unbalanced loads. The information system is a solution that serves as a workload analysis calculation tool. Therefore, the researcher designed an Android-based WMA (Workload Measurement Analysis) application. The WMA application was developed using the waterfall system method, which consists of stages of analysis, design, coding, and testing. This application displays several features, including the login menu, homepage, learn, input data, conclusion, and history. In the homepage display, there are three preferred methods for calculating workloads: the WISN (Workload Indicator Staffing Need) method and ABK-Kes (Workload Analysis for Healthcare Industry) method for the healthcare sector. The WMA application was tested using the TAM (Technology Acceptance Model) method. Thus, it can be concluded that the informants are very satisfied with the ease and usefulness variables of the WMA (Workload Measurement Analysis) application. The WMA application is ready to be used in the healthcare sectors to help analyze workload calculations. Keywords: WMA application, TAM method, workload calculation.